2017
DOI: 10.1093/neuonc/nox168.868
|View full text |Cite
|
Sign up to set email alerts
|

Rare-19. Multicenter, Phase 2 Study of Bevacizumab in Children and Adults With Neurofibromatosis 2 and Progressive Vestibular Schwannomas: An Nf Clinical Trials Consortium Study

Abstract: NEURO-ONCOLOGY • NOVEMBER 2017 able cases BRAF mutation was noted. Adjuvant radiation was delivered in 67 (27.7%) patients. Estimated median PFS was 48.3 months. In univariate analysis younger patients (≤20 years) had better PFS compared to elder [103.2 vs 36 months (p= .013]. Patients with GTR and grade II tumor had better PFS than STR and grade III tumor [84 vs14 months; p=0.001]; [48 vs 11.7 months p=0.000]. Ki 67 index ≤5% conferred better PFS [144 vs 17 months; p=0.250]. Estimated median OS was 209.0 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Moreover, complications related to wound healing have been well-documented in patients undergoing anti-angiogenic treatment. This result has been strongly supported by studies like those conducted by Ahn et al, 23 Plotkins et al, 24 and also Clark et al, 25 which have shown results that appear similar to ours, highlighting complications in wound healing among patients treated with anti-angiogenics. Furthermore, both human and animal histopathological studies have demonstrated a decrease in endothelial cells and macrophages, reduced neovascularization, disruption of re-epithelialization, and impairment of wound healing [26][27][28] .…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, complications related to wound healing have been well-documented in patients undergoing anti-angiogenic treatment. This result has been strongly supported by studies like those conducted by Ahn et al, 23 Plotkins et al, 24 and also Clark et al, 25 which have shown results that appear similar to ours, highlighting complications in wound healing among patients treated with anti-angiogenics. Furthermore, both human and animal histopathological studies have demonstrated a decrease in endothelial cells and macrophages, reduced neovascularization, disruption of re-epithelialization, and impairment of wound healing [26][27][28] .…”
Section: Discussionsupporting
confidence: 92%
“…A recent study has tackled the question of maintenance therapy with Bevacizumab in a prospective trial of 20 patients receiving 5 mg/kg every 3 weeks for 18 months. They demonstrated that low-dose Bevacizumab remained effective in preventing hearing decline (70% of freedom from hearing loss after 98 weeks) and tumor growth (89% of freedom from tumor growth after 98 weeks) while maintaining quality of life and offering good tolerance, with three participants (15%) discontinuing treatment due to adverse events [35 ▪ ].…”
Section: Therapeutic Aspects Of Schwannomatosismentioning
confidence: 99%